Induction of STAT3-Dependent CXCL5 Expression and Neutrophil Recruitment by Oncostatin-M during Pneumonia - Traber, Katrina E. (Am J Respir Cell Mol Biol, 2015)
Acute bacterial pneumonia is a significant public health concern worldwide. Understanding the signals coordinating lung innate immunity may foster the development of therapeutics that limit tissue damage and promote host defense. We have previously shown that lung messenger RNA expression of the IL-6 family cytokine oncostatin-M (OSM) is significantly elevated in response to bacterial stimuli. However, its physiological significance during pneumonia is unknown. Here we demonstrate that OSM is rapidly increased in the airspaces of mice after pulmonary infection with Escherichia coli. Neutralization of OSM caused a substantial decrease in airspace neutrophils and macrophages. OSM blockade also caused a marked reduction in lung chemokine (C-X-C motif) ligand (CXCL) 5 expression, whereas other closely related neutrophil chemokines, CXCL1 and CXCL2, were unaffected. Intratracheal administration of recombinant OSM was sufficient to recapitulate the effect on CXCL5 induction, associated with robust activation of the signal transducer and activator of transcription 3 (STAT3) transcription factor. Cell sorting revealed that OSM effects were specific to lung epithelial cells, including a positive feedback loop in which OSM may facilitate expression of its own receptor. Finally, in vitro studies demonstrated that STAT3 was required for maximal OSM-induced CXCL5 expression. These studies demonstrate a novel role for OSM during pneumonia as an important signal to epithelial cells for chemokine induction mediating neutrophil recruitment.